LEGAL REGULATION OF STUDENT SELF-GOVERNMENT UNDER THE CONDITIONS OF THE MARITAL STATE - Stanislav Vasiliev (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
The scientific article is devoted to the peculiarities of the legal regulation of student self-government in higher education institutions of Ukraine under martial law. The relevance of the selected issues is related to the need to take into account the new operating conditions of higher education institutions under martial law during the development of legislative and by-laws that will regulate educational activities. The legislative and by-laws, which establish the conditions of activity of student self-government bodies, have been studied. The scientific novelty of the study consists of determining recommendations for improving the legal regulation of the work of student self-government bodies under martial law.Peculiarities of the legal regulation of the activity of student parliaments in the conditions of martial law are the remote holding of elections to student self-government bodies and remote meetings of elected student councils. Interaction between the administration of the institution of higher education and the leadership of the student council should also take place remotely.To improve the legal regulation of the activities of student self-government bodies, it is proposed to provide the following norms in the local provisions on student self-government of each institution of higher education. Establish that elections of student self-government bodies and meetings of student parliaments in martial law conditions are conducted using remote communication. To establish that the activity of student councils of individual dormitories is suspended until the time of resumption of full-time education. Provide for the publication of decisions of student councils on the website of the institution of higher education on a specially created electronic page. Among the tasks of student self-government, assistance to higher education seekers from internally displaced persons or involvement of students in volunteer activities may be introduced.